Development and quality evaluation of spent hen meat spread incorporated with corn starch - Ranade, Ashlesha; Malav, Om Prakash; Mehta, Nitin; Wagh, Rajesh V.; Sharma, Rajnish (Journal of Meat Science, 2023)
Three different levels of corn starch i.e. 4%, 6% and 8% was incorporated after replacing meat in the formulation of spent hen meat spread (SHMS). The lowest scores for most of the sensory parameters were observed in product with 4% level of corn starch whereas the product with 6% corn starch level had highest scores for all the sensory parameters. Lightness values of SHMS increased significantly (P
Keywords: Acceptability; instrumental colour profile; Proximate composition; Starch; Sensory quality